2022
DOI: 10.1029/2021tc006893
|View full text |Cite
|
Sign up to set email alerts
|

From Crystals to Crustal‐Scale Seismic Anisotropy: Bridging the Gap Between Rocks and Seismic Studies With Digital Geologic Map Data in Colorado

Abstract: Deep continental crustal structures are enigmatic due to lack of direct exposures and limited tools to investigate them remotely. Seismic waves can sample these rocks, but most seismic methods focus on coarse crustal structures while laboratory measurements concentrate on crystal‐scale rock properties, and little work has been conducted to bridge this interpretation gap. In some places, geologic maps of crystalline basement provide samples of the intermediate‐scale fabrics and structures that may represent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 145 publications
(211 reference statements)
0
5
0
Order By: Relevance
“…The complicated and azimuthally varying RF waveforms shown in their paper, however, indicate the breakdown of this assumption. Similar RF signals have been used elsewhere to infer lithospheric anisotropy and its tectonic implications (e.g., Audet, 2015;Bar et al, 2019;Birkey et al, 2021;Bourke et al, 2020;Chen et al, 2021;Frothingham et al, 2022;Gosselin et al, 2021;Levin et al, 2021;Nikulin et al, 2019;Olugboji et al, 2016;Salimbeni et al, 2021;Schulte-Pelkum et al, 2021;Sherrington et al, 2004;Vergne et al, 2003). In addition, the small number of RF measurements (<20-60 for more than half of stations) considered in Syuhada et al (2016) may lead to uncertainties in their results.…”
mentioning
confidence: 96%
“…The complicated and azimuthally varying RF waveforms shown in their paper, however, indicate the breakdown of this assumption. Similar RF signals have been used elsewhere to infer lithospheric anisotropy and its tectonic implications (e.g., Audet, 2015;Bar et al, 2019;Birkey et al, 2021;Bourke et al, 2020;Chen et al, 2021;Frothingham et al, 2022;Gosselin et al, 2021;Levin et al, 2021;Nikulin et al, 2019;Olugboji et al, 2016;Salimbeni et al, 2021;Schulte-Pelkum et al, 2021;Sherrington et al, 2004;Vergne et al, 2003). In addition, the small number of RF measurements (<20-60 for more than half of stations) considered in Syuhada et al (2016) may lead to uncertainties in their results.…”
mentioning
confidence: 96%
“…Recent structural analyses by Frothingham et al. (2022) observed that surficial fault traces and ductile fabrics in Colorado have a dominantly southeast‐northwest orientation, and that these fabrics continue at depth where they can act as focal planes for magmatism. It is not clear why this southeast‐northwest magmatic fabric was not present between 35 and 25 Ma (Figure 7, left panels).…”
Section: Discussionmentioning
confidence: 99%
“…The regional southeast-northwest alignment of magma centers between the early ignimbrite flare-up (40 to 35 Ma; Figure 8b) and again during Rio Grande rift formation (25 to 20 Ma; Figure 8c) is subparallel to Paleo-and Mesoproterozoic structures that were reactivated during the Laramide orogeny (Tweto, 1975). Recent structural analyses by Frothingham et al (2022) observed that surficial fault traces and ductile fabrics in Colorado have a dominantly southeast-northwest orientation, and that these fabrics continue at depth where they can act as focal planes for magmatism. It is not clear why this southeast-northwest magmatic fabric was not present between 35 and 25 Ma (Figure 7, left panels).…”
Section: Regional-scale Processesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, despite igneous rocks making up significant portions of continental crust (Figure 1), magmatic fabrics are generally underrepresented in crustal seismic anisotropy studies and bulk rock elastic tensor databases (Brownlee et al., 2017). Accordingly, the studies that use such databases to predict and interpret crustal seismic anisotropy (e.g., Frothingham et al., 2022; Moschetti et al., 2010; Okaya et al., 2018) also tend to propagate this bias toward solid‐state deformation.…”
Section: Introductionmentioning
confidence: 99%